Induction of ovarian maturation and spawning by combined treatment of serotonin and a dopamine antagonist, spiperone in Litopenaeus stylirostris and Litopenaeus vannamei - Alfaro, Jorge (2004)
The study was designed to develop a reliable technique for inducing ovarian maturation and spawning in Litopenaeus stylirostris and Litopenaeus vannamei, as an alternative to the traditional and destructive eyestalk ablation. Two combinations of molecules were evaluated: (a) serotonin (5- HT) at 50 Ag g 1 body weight (b.w.) + juvenile hormone (JH III) at 227 ng g 1 b.w., and (b) 5-HT at 25 Ag g 1 b.w. + 1.5 or 5 Ag g 1 b.w. spiperone. Combination (a) was tested in wild L. stylirostris, generating no ovarian maturation. Combination (b) did induce maturation and spawning in wild L. stylirostris and pond-grown L. vannamei. Maturation was observed in both 5-HT/spiperone treated females, as well as in vehicle injected females and in non-treated non-injected neighboring females, at rates similar to those obtained with eyestalk ablation. There was no significant difference in the quality of spawns between treatment groups. It is proposed that the combined injection of 5-HT and spiperone not only induces maturation and spawning, but also stimulates the release of maturation promoting pheromones into the water. The technique should be further tested at private facilities to define its commercial relevance for nauplii production. D 2003 Elsevier B.V. All rights reserved.